Preauricular solitary fibrous tumor: A case report of uncommon neoplasm arising from the facial region. Issue 3 (May 2020) - Watanabe, Masato; Kohno, Michihide; Hasegawa, On; Kawase-Koga, Yoko; Chikazu, Daichi; Enomoto, Ai; Nagao, Toshitaka
Abstract: Solitary fibrous tumor (SFT) is a rare neoplasm morphologically characterized by spindle cell proliferation. SFTs mostly arise from the pleura, but also involve a wide variety of the extrapleural organs. Especially, the development in the facial region is extremely rare. We describe an extremely rare case of SFT in the left preauricular region. The tumor lesion had gradually grown without pain or facial paralysis. Magnetic resonance imaging scan showed a circumscribed mass with high signal intensity on Gd-DTPA-enhanced T1-weighted images measuring approximately 3.0 cm in diameter. The tumor lesion was excised completely. Histological examination of the surgical specimen revealed proliferation of spindle tumor cells with a patternless pattern. Various amounts of collagen bundles intervened in the spindle tumor cells. The cellular atypia of the tumor cells was weak. Immunohistochemical studies showed strongly positive immunoreactivities for CD34, vimentin, and bcl-2. CD117 and STAT6 were also positive. The expression rates of nuclear staining for Ki-67 of the tumor cells were less than 1 %. Finally, a definitive diagnosis of SFT was made on the basis of the microscopic and immunohistochemical features. There was no recurrence or metastasis after surgical resection and the outcome was good. It is suggested that SFT should be included in the differential diagnoses for mesenchymal tumor of subcutaneous area adjacent to the parotid gland. We consider that a better understanding of the immunohistochemical profile of SFT in the facial subcutaneous region may play a useful role in making a definitive diagnosis.